HUBUNGAN KOMUNIKASI EFEKTIF SBAR DENGAN INSIDEN KESELAMATAN PASIEN DI RUANG RAWAT INAP RSUD DEPOK - Mugia Saida Daruini (2021)
Patient safety incidents are things that must be avoided by nurses so that they must be considered in implementing the six patient safety goals. Effective communication is one component of patient safety goals, so it needs to be applied by nurses in providing nursing care. The purpose of this study was to determine the relationship between effective communication and patient safety incidents in the Inpatient Room at RSUD Depok. This study used a cross sectional research design. The population in this study were nurses in the Inpatient Room at RSUD Depok. The sampling technique in this study used a total sampling technique with a sample of 48 respondents. Data analysis in this study used Chi Square with p-value = 0.032 (p-value <0.05), which means that there is a relationship between effective communication and patient safety incidents. Nurses who have good effective communication have a higher chance of not committing a patient safety incident. Researchers suggest nurses to be able to implement effective communication better so that patient safety incidents can be prevented or reduced. Keyword : Effective Communication, Patient Safety Incident